Odpowiedzi

Najlepsza Odpowiedź!
2010-02-18T10:12:28+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(1/3 - a)=-a+3a
e) (t-2s-1)7=7t-14s-7
f) ½ (2a-4b+1)=a-2b+0,5
g) m(2m+3)=2m+3m=5m
h) 3p(2r+5p-1)=6pr+15p²-3p=6pr+12p
i) xy(2x-3y+5)=2x²y-3xy²+5xy
9 4 9
2010-02-18T10:17:26+01:00
A) 3(a-2) = 3a-6
b) -4(x+y) = -4x - 4y
c) -5(-x+1) = 5x-5
d) -3a(1/3 - a) = -a - 2a
e) (t-2s-1)7 = 7t-14s-7
f) ½ (2a-4b+1) = a-2b +½
g) m(2m+3) =2m² +3m
h) 3p(2r+5p-1) = 6pr +15p²-3p
i) xy(2x-3y+5) = 2x²y -3xy²+5xy
4 5 4
2010-02-18T10:17:30+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(1/3 - a)=-a+3a²
e) (t-2s-1)7=7t-14s-7
f) ½ (2a-4b+1)=a-3b+1/2
g) m(2m+3)=2m²+3m
h) 3p(2r+5p-1)=6pr+15p²-3p
i) xy(2x-3y+5)=2x²y-3xy²+15xy

nie wiem czy dobrze ;p
4 5 4